Family type and family size as correlates of parents’/guardians’ disposition towards girl-child education in Tertiary Institutions in Delta State, Nigeria - Igbineweka, Martins Noyosase; Omoragbon, Ebuwa; Omamuli-Igbinoba, Okeoghene O. (Universitas Mercu Buana Yogyakarta, 2023)
The study investigated Family type and Family size as correlates of parents'/guardians' disposition towards girl-child education amongst female students in public tertiary institutions in Delta state, Nigeria. Two research aims, with their corresponding advantages were raised and tested at 0.05 alpha levels. Correlational survey design was used with a population was ten thousand five hundred and thirty-six (10,536) female students from three (3) public tertiary institutions, with a sample of 250 female students. The multistage sampling technique was adopted and a questionnaire titled